Loss of Yap/Taz in cardiac fibroblasts attenuates adverse remodelling and improves cardiac function. Issue 7 (16th June 2021) - Mia, Masum M; Cibi, Dasan Mary; Ghani, Siti Aishah Binte Abdul; Singh, Anamika; Tee, Nicole; Sivakumar, Viswanathan; Bogireddi, Hanumakumar; Cook, Stuart A; Mao, Junhao; Singh, Manvendra K
Abstract: Aims: Fibrosis is associated with all forms of adult cardiac diseases including myocardial infarction (MI). In response to MI, the heart undergoes ventricular remodelling that leads to fibrotic scar due to excessive deposition of extracellular matrix mostly produced by myofibroblasts. The structural and mechanical properties of the fibrotic scar are critical determinants of heart function. Yes-associated protein (Yap) and transcriptional coactivator with PDZ-binding motif (Taz) are the key effectors of the Hippo signalling pathway and are crucial for cardiomyocyte proliferation during cardiac development and regeneration. However, their role in cardiac fibroblasts, regulating post-MI fibrotic and fibroinflammatory response, is not well established. Methods and results: Using mouse model, we demonstrate that Yap/Taz are activated in cardiac fibroblasts after MI and fibroblasts-specific deletion of Yap/Taz using Col1a2 Cre(ER)T mice reduces post-MI fibrotic and fibroinflammatory response and improves cardiac function. Consistently, Yap overexpression elevated post-MI fibrotic response. Gene expression profiling shows significant downregulation of several cytokines involved in post-MI cardiac remodelling. Furthermore, Yap/Taz directly regulate the promoter activity of pro-fibrotic cytokine interleukin-33 ( IL33 ) in cardiac fibroblasts. Blocking of IL33 receptor ST2 using the neutralizing antibody abrogates the Yap-induced pro-fibrotic response in cardiac fibroblasts. We demonstrate that the altered fibroinflammatory programme not only affects the nature of cardiac fibroblasts but also the polarization as well as infiltration of macrophages in the infarcted hearts. Furthermore, we demonstrate that Yap/Taz act downstream of both Wnt and TGFβ signalling pathways in regulating cardiac fibroblasts activation and fibroinflammatory response. Conclusion: We demonstrate that Yap/Taz play an important role in controlling MI-induced cardiac fibrosis by modulating fibroblasts proliferation, transdifferentiation into myofibroblasts, and fibroinflammatory programme. Graphical Abstract: